Rheological response of a modified polyacrylamide–silica nanoparticles hybrid at high salinity and temperature. Issue 44 (9th October 2020) - Mirzaie Yegane, Mohsen; Hashemi, Fatemeh; Vercauteren, Frank; Meulendijks, Nicole; Gharbi, Ridha; Boukany, Pouyan E.; Zitha, Pacelli
Abstract : Hybrid of hydrophobically modified polyacrylamide–silica nanoparticles emerged as a promising strategy for achieving enhanced stability and high viscosity. Abstract : Water-soluble polyacrylamides have often been used to modify flow response in various water-based technologies and industrial processes, including paints, water treatment, paper manufacturing, and chemical enhanced oil recovery. Polymers are susceptible to degradation at combined high salinity and elevated temperature conditions which limits their overall performance. Hybrid mixtures of hydrophobically modified polyacrylamide (HMPAM) with hydrophobically modified silica nanoparticles (NPs) emerged as a promising strategy for achieving enhanced stability and high viscosity in brines having a high total dissolved solids (TDS) content and high hardness at elevated temperatures (>20 wt% TDS, including >1.5 wt% divalent cations at T > 70 °C). The rheological response of the hybrids at various concentrations of HMPAM and NPs was examined to investigate the synergic effects. Hybridization of HMPAM with NPs led to a higher viscosity at high salinity and elevated temperature. The viscosity improvement was more pronounced when the concentration of HMPAM was in the semi-dilute regime and concentration of NPs was higher than a critical threshold where the viscosity increased roughly by a factor of 1.5. Here we present the mechanisms of improved viscosity behaviour. The rheological data suggest the role of NPs in the bridging between HMPAM molecules, which in turn increases the hydrodynamic radius and consequently the viscosity of the hybrids.